Analysis of mycophenolic acid from saliva samples after its purification with the method of solidliquid extraction - Otašević Biljana; Protić Ana; Golubović Jelena; Zečević Mira; Cerović Milica; Bralović Ljubica (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Pharmacological effect of a drug depends on its free fraction in plasma. By certain drugs, like immunosupresive mycophenolic acid, concentrations below therapeutic lead to rejection of the transplanted organ while concentrations above therapeutic lead to toxic effects, primarily on kidney and liver. For this reason constant monitoring of mycophenolic acid in plasma is necessary. Concerning frequency of sampling, availability and non-invasive way of sampling, saliva presents one of the best biological materials for analysis. On the other hand, numerous interfering endogen substances, impurities and high viscosity of saliva make this biological material difficult for purification. Mycophenolic acid has to be purified and concentrated from saliva to be consequently determined applying appropriate analytical method. In this paper solid phase extraction method for purification of saliva has been presented. The efficacy of solid phase extraction has been influenced by many different experimental parameters, so these parameters has to be strongly controlled, and protocol of extraction procedure has been proposed. In this way conditioning of polymeric sorbent has been done with methanol and purified water, samples have been applied together with 0.1 % formic acid, washing has been done with purified water and elution of mycophenolic acid has been performed with acetonitrile and 0.2% formic acid.